2008
DOI: 10.1016/s1607-551x(08)70088-3
|View full text |Cite
|
Sign up to set email alerts
|

Socrates, Problem‐based Learning and Critical Thinking—A Philosophic Point of View

Abstract: Problem‐based learning (PBL) is a learner‐centered educational method based on the principles of heuristics and collaboration. It has been considered an effective learning method in general and in professional education, especially in medical education. This article analyzes the thinking structure and philosophical background of PBL through the educational ideas of Socrates and the truth conception of Karl Popper. In the different phases of the PBL process, various truth conceptions will help to formulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 10 publications
0
18
0
2
Order By: Relevance
“…In education, we highlight pioneering authors who have emphasized critical thinking (although with other terminologies), from the Greek philosopher Socrates and the concepts of "knowledge" and "maièutica," to the American philosopher, psychologist, and educator John Dewey, and reflection on "thinking" and "reflecting" [23,24].…”
Section: The Importance Of Critical Thinking In Educationmentioning
confidence: 99%
“…In education, we highlight pioneering authors who have emphasized critical thinking (although with other terminologies), from the Greek philosopher Socrates and the concepts of "knowledge" and "maièutica," to the American philosopher, psychologist, and educator John Dewey, and reflection on "thinking" and "reflecting" [23,24].…”
Section: The Importance Of Critical Thinking In Educationmentioning
confidence: 99%
“…In a problem based learning process, students work together and structure their own knowledge by inquiring, searching and problem solving. Thus, it is possible to say that the foundations of problem based learning depend upon cooperative learning principles (Wang et al, 2008). Problem based learning emphasizes self learning, because it requires students to direct their own learning (Finch, 1999).…”
Section: Problem Based Learningmentioning
confidence: 99%
“…Students who work in groups try to define the problem's situation, understand the problem, communicate each other, and define the knowledge needed to solve the problem (Yuan, Williams, & Fan, 2008). After students define their issues, they focus on solving the problem (Wang et al, 2008). In problem based learning students direct their own learning by exchanging views, instead of teacher centred learning (Delisle, 1997).…”
Section: Problem Based Learningmentioning
confidence: 99%
“…Five thousand years ago the philosophical writings 'The Upanishads' recommended learning through discussion of everyday problems (Mascaro 1965). Socrates taught so powerfully through questions that arose from everyday living, that he was executed for being too influential (de Botton 2001, Wang et al 2008. In the 20th Century, Dewey argued that children learn more in a kitchen than a classroom (Dewey 1938), while Piage, Montesori and Steiner developed progressive and practical educational methods through real-life engagement rather than theoretical, teacher-led desk-based lessons (Sadlo 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A study of nursing students found that PBL in a practice setting built the skill of seeing the theory within everyday practice (Chikotas 2009), which is the first stage of being able to perceive gaps in one's own knowledge (Firestein 2012). An excitement towards gaining new understanding is a prerequisite to meaningful learning (Wang et al 2008). The supportive culture of PBL enables students to acknowledge what they do not know, to activate further learning (Dangerfield et al 2007).…”
Section: Introductionmentioning
confidence: 99%